An investigation of the presence and antimicrobial susceptibility of Enterobacteriaceae in raw and cooked kibble diets for dogs in the United Kingdom - Morgan, Genever; Pinchbeck, Gina; Taymaz, Eda; Chattaway, Marie Anne; Schmidt, Vanessa; Williams, Nicola (Frontiers in Microbiology, 2024)
Raw meat diets (RMD) for dogs are an increasingly popular alternative pet food choice, however studies worldwide have demonstrated them to be contaminated with zoonotic and antimicrobial resistant (AMR) bacteria, including bacteria resistant to critically important antibiotics. Despite this, few data exist surrounding the presence of these bacteria in RMD in the United Kingdom. The present study aimed to identify the most commonly selected RMD and non-raw diets (NRMD) by UK dog owners. Additionally, it investigated the presence of AMR-Enterobacteriaceae in samples of preprepared RMD and cooked commercial kibble dog foods.An online survey investigating diet preferences of UK dog owners was open for six weeks between February-March 2020. From this, the top ten brands of pre-prepared raw and cooked kibble diets were ascertained and 134 samples purchased (110 RMD, 24 kibble) and subjected to microbiological testing. Bacterial enumeration of E. coli and other Enterobacteriaceae was undertaken, and the presence of Salmonella spp. and AMR-E. coli within samples determined. Whole genome sequencing was undertaken on Salmonella spp. and third-generation cephalosporin-resistant 3GCR-E. coli isolates.Pre-prepared RMD was most commonly selected by dog owners who fed RMD, and cooked commercial complete dry food was most frequently fed by owners who fed NRMD. Damaged and leaking packaging was observed in samples of RMD, alongside variability in information provided surrounding product traceability. Counts of E. coli and other Enterobacteriaceae exceeding >5000 CFU/g were identified in samples of RMD. AMR-, extended-spectrum beta-lactamase (ESBL)-producing and 3GCR-E. coli was isolated from 39%, 14% and 16% of RMD samples, respectively. Multiple antimicrobial resistance genes were identified in 3GCR-E. coli isolates. Of the ESBL encoding genes, blaCTX-M-15 was most commonly identified. S. enterica was isolated from 5% of RMD samples. No Enterobacteriaceae were isolated from any of the cooked kibble samples.The present study suggests that pre-prepared RMD available for dogs in the UK can be contaminated with zoonotic and AMR-Enterobacteriaceae. RMDs, therefore, are potentially an important One Health concern. Veterinary and medical professionals, pet food retailers and pet owners should be aware of these risks; and stringent hygiene measures should be practiced if owners choose to feed RMD.